EXTRACURRICULAR FINANCIAL PLANNING MANAGEMENT AT SOUTH TANGERANG SMA: STRATEGIC STEPS FOR EFFICIENCY AND TRANSPARENCY - Noryani, Noryani; Novita, Dina; Supatmin, Supatmin (Yayasan Education and Social Center, 2024)
This research aims to analyze the influence of facilities and infrastructure management on teacher performance in schools. This research uses a quantitative approach with survey methods. The sample used was 100 teachers from several schools in the Medan area. Data was collected using a questionnaire that measured facilities and infrastructure management variables as well as teacher performance. The research results show that the management of facilities and infrastructure has a positive and significant influence on teacher performance. Adequate facilities and infrastructure, such as comfortable classrooms and complete facilities, can create an environment that is conducive to the learning process, which in turn improves teacher performance. Apart from that, the school principal as manager of facilities and infrastructure has a key role in ensuring that existing facilities can support learning activities. This research also emphasizes that good management of facilities and infrastructure must be carried out transparently and efficiently, involving all related parties, including the government and the community. These findings contribute to the development of education management in Indonesia, especially in terms of facility management to support teacher performance.